EP19 Hyperferritinaemia causes in a UK district general hospital. (20th April 2020) - Fieldman, Tom; Stimson, Laura; Zeb, Shabeena; Alderson, Steven; Lloyd, Mark
Abstract: Background: Hyperferritinaemia has multiple causes including iron overload, liver disease, and systemic inflammation either in the context of infection, autoimmunity, or malignancy. Marked hyperferritinaemia has been used to aid diagnosis of rare autoimmune conditions such as adult onset Still's disease. Methods: Patients with plasma ferritin concentrations over 3000 μg/L from 7 April 2014 until 30 August 2019 (just over 5 years) in a district general hospital were identified. Those without sufficient documentation to identify the likely causes of hyperferritinaemia were excluded. Included patients (n = 283) were grouped according to maximum ferritin concentration, and likely causes of hyperferritinaemia from the following list were classified as follows: Infection; solid organ malignancy; haematological malignancy, autoimmune disease; transfusion dependence; liver disease, renal failure, haemolytic anaemia. Results: The most common causes of hyperferritinaemia were infection (31%), solid organ malignancy, (28%), haematological malignancy (23%), and liver disease (22%). Peak ferritin concentration did not appear to be strongly associated with the factors that caused it. To explore the diagnostic utility of ferritin to distinguish autoimmune processes, infection, malignancy, and liver disease, an association between these factors and maximum ferritin concentration was tested for using Fisher's exact test. No statistically significant association was found (p = 0.8967). Conclusion: We found no association between maximum ferritin concentration and the causes thereof, however this study does not elucidate the diagnostic utility of hyperferritinaemia since most of the patients studied had established diagnoses before their hyperferritinaemia was identified. Hyperferritinaemia appears to be a marker of severe disease, in that most of the patients studied had died by the time of data collection. Disclosures: T. Fieldman None. L. Stimson None. S. Zeb None. S. Alderson None. M. Lloyd None.